2012
DOI: 10.1088/0004-637x/754/2/90
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Satellite Galaxy Stellar Mass Loss and Predicting Intrahalo Light. I. Framework and Results at Low Redshift

Abstract: We introduce a new technique that uses galaxy clustering to constrain how satellite galaxies lose stellar mass and contribute to the diffuse "intrahalo light" (IHL). We implement two models that relate satellite galaxy stellar mass loss to the detailed knowledge of subhalo dark matter mass loss. Model 1 assumes that the fractional stellar mass loss of a galaxy, from the time of merging into a larger halo until the final redshift, is proportional to the fractional amount of dark matter mass loss of the subhalo … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 138 publications
4
37
0
Order By: Relevance
“…By itself this is an interesting point because abundance matching and age matching yield galaxy populations with clustering statistics that are broadly similar to those observed in large-scale galaxy surveys (e.g. Kravtsov et al 2004;Vale & Ostriker 2004;Tasitsiomi et al 2004;Vale & Ostriker 2006;Conroy & Wechsler 2009;Guo et al 2010;Simha et al 2010;Neistein et al 2011;Watson et al 2012;Rodríguez-Puebla et al 2012;Kravtsov 2013;. This suggests that the assembly bias predicted by abundance matching may not be wildly different from what is observationally permissible.…”
Section: Discussionmentioning
confidence: 59%
“…By itself this is an interesting point because abundance matching and age matching yield galaxy populations with clustering statistics that are broadly similar to those observed in large-scale galaxy surveys (e.g. Kravtsov et al 2004;Vale & Ostriker 2004;Tasitsiomi et al 2004;Vale & Ostriker 2006;Conroy & Wechsler 2009;Guo et al 2010;Simha et al 2010;Neistein et al 2011;Watson et al 2012;Rodríguez-Puebla et al 2012;Kravtsov 2013;. This suggests that the assembly bias predicted by abundance matching may not be wildly different from what is observationally permissible.…”
Section: Discussionmentioning
confidence: 59%
“…The absence or mildness of these trends is also confirmed at lower redshifts, i.e., z < 0.3, (Zibetti et al 2005;Krick & Bernstein 2007). These findings are inconsistent with most of the previous results from both cosmological and analytical simulations, which generally agree with an increasing ICL fraction as cluster mass grows (Murante et al 2004;Lin & Mohr 2004;Purcell et al 2007;Watson et al 2012). However, recent simulations suggest a much weaker dependence of the ICL fraction on cluster mass (Murante et al 2007;Dolag et al 2010;Puchwein et al 2010;Martel et al 2012;Cui et al 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Conroy et al 2006;Behroozi et al 2010;Guo et al 2010;Moster et al 2010;Wetzel & White 2010;TrujilloGomez et al 2011;Watson, Berlind & Zentner 2012;Nuza et al 2013;Reddick et al 2013). For instance, Conroy et al (2006) showed that SHAM reproduces the observed galaxy clustering over a broad redshift interval (0 < z < 5).…”
Section: Introductionmentioning
confidence: 99%